The potential of the antifungal nystatin to be repurposed to fight the protozoan Trypanosoma cruzi - Maciel, Belén Jesús; Reigada, Chantal; Digirolamo, Fabio Augusto; Rengifo, Marcos; Pereira, Claudio Alejandro; Miranda, Mariana Reneé; Sayé, Melisa (Frontiers in Microbiology, 2025)
Chagas disease, caused by the parasite Trypanosoma cruzi, affects 6 million people worldwide. Although the drugs benznidazole (BZN) and nifurtimox are available to treat Chagas, they are not effective in the chronic phase when most patients are diagnosed. Moreover, long-term regimen and severe side effects often lead to poor adherence and treatment abandonment. These problems highlight the urgent need to develop new therapies to treat this neglected disease. Given that the antifungal drug nystatin (NYS) affects arginine uptake in yeasts, and fluctuations on arginine availability through transport processes in T. cruzi can negatively affect its viability, in this work we evaluated the potential of NYS for drug repurposing against T. cruzi. NYS inhibited arginine uptake and presented trypanocidal effect in both epimastigotes (IC50 0.17 μM) and trypomastigotes (IC50 4.90 μM). In addition, treatment of infected cells with NYS decreased the release of trypomastigotes with better efficacy than BZN (IC50s 4.83 μM and 8.60 μM, respectively) suggesting that NYS affects the progression of the intracellular life cycle. Furthermore, we observed a synergistic effect both in isolated trypomastigotes and infected cells when NYS was combined with BZN, which could enhance efficacy while improving treatment safety and adherence. As in yeasts, the mechanism of action of NYS in T. cruzi involved the plasma membrane disruption, and membrane transport processes, like amino acids and thymidine uptake, were affected prior to the disruption probably due to NYS interaction with the membrane. Drug repurposing is a recommended strategy by the World Health Organization to develop new therapeutic alternatives for neglected diseases. Our results indicate that NYS presents great potential to be repurposed as a trypanocidal drug to fight T. cruzi.